Energy expenditure of Saanen and Anglo-Nubian goats at different temperatures - Lima, Ana Rebeca Castro [UNESP]; Fernandes, Marcia Helena Machado da Rocha [UNESP]; Silveira, Raiza Felismino [UNESP]; Biagioli, Bruno [UNESP]; Teixeira, Izabelle Auxiliadora Molina de Almeida [UNESP]; Resende, Kleber Tomás de [UNESP] (Elsevier, 2020)
This study aimed to determine the effect of temperature on energy balance of Saanen and Anglo-Nubian goats, using indirect open circuit respirometry. Six non-lactating and non-pregnant Saanen goats (initial body weight [BW] of 53.7 ± 7.7 kg) and Anglo-Nubian goats (initial BW of 56.4 ± 8.0 kg) were randomly assigned to three groups. Each group was allocated in climatic rooms and randomly assigned to three different room temperatures (treatments) in three 28-d periods, including 20 days for adaptation and eight days for measurements. Treatments consisted of three controlled room temperatures: 10 °C ± 0.23 and 88.10 % ± 0.99 relative humidity (RH), 20 °C ± 0.41 and 80.75 % ± 4.13 RH, and 35 °C ± 1.05 and 45.58 % ± 5.07 RH. Within each 8-day period, metabolism trial and gaseous exchange measurements were performed for five days (from day 21 to day 25). After day 25, goats were subjected to 60-h fasting, with subsequent gas exchange measurement to estimate fast heat production (FHP). Irrespective of breed, the dry matter intake (DMI) and the organic matter intake (OMI) decreased linearly as the temperature increased from 10 to 35 °C. Apparent digestibility of the nutrients showed the lowest values at 20 °C. Respiratory rate (RR) and respiratory volume increased with increasing ambient temperature. At 35 °C, methane production of Saanen goats was higher than Anglo-Nubian goats, and metabolizable energy (ME) and metabolizability (q) of Saanen goats were lower than Anglo-Nubian goats. The daily FHP above 20 °C decreased 8.7 kJ/kg0.75 BW for each degree as the temperature increased up to 35 °C, and below 20 °C decreased 5.4 kJ/kg0.75 BW as the temperature decreased up to 10 °C. Both breeds can maintain homeostasis in ambient temperature between 10 and 35 °C; however, Anglo-Nubian goats seem to cope better in adverse conditions of heat than Saanen goats.
Keywords: Energy metabolism; Fast heat production; Methane; Net energy; Respirometry